RELATIONSHIP OF THE SELF AND THE STRATIFIED LAYER IN SOME TELECOMMUNICATIONS TERMS (Scientific journal of the Fergana State University, 2023)
The article was written about telecommunication terms in Uzbek language, which were formed with native words and loanwords.